AGE AND KNOWLEDGE OF STROKE PATIENT CARE FOR CARE PROVIDERS - Mohamad Khafidh Rio Irwansyah; Muhammad Hasan Burhanudin; Heny Siswanti; Muhamad Jauhar (Universitas Muhammadiyah Kudus, 2024)
For families who are caring for post-stroke, it is important to know the impacts that arise and the potential for complications in the patient. Recovery for stroke sufferers is difficult to achieve properly if no one in the family understands what needs to be done to improve the health status of post-stroke patients and that appropriate care is given to family members who have suffered a stroke. There are many factors that can influence a person's knowledge, one of the factors is age. To find out the relationship between age and family knowledge about post-stroke patient care. The research is correlational research, independent variable (family knowledge) and dependent (age) the respondents was 30 respondents total sampling , Inclusion Criteria; Family of patients, Willing to be respondents, Aged ≥18 years, Can communicate well, Has direct involvement in patient care, Exclusion criteria; Families who are unwilling to participate, have cognitive or communication disorders, have health conditions such as serious mental disorders or chronic diseases. Research Instruments use Questionnaires. Results of statistical analysis of tests spearmen rho obtained p value = 0.017 is smaller than the significance level value ɑ 0.05. then Ho is rejected and Ha is accepted. It can be concluded that there is a relationship between the respondent's age and family knowledge about post-stroke patient care. The hope is that future researchers can increase the number of samples not only in one hospital.